Surgical treatment for spondylitis caused by non-tuberculous mycobacteria with extensive abscess. A report of two cases - Fushimi, Kazunari; Nozawa, Satoshi; Masuda, Kazuaki; Akiyama, Haruhiko; Sawada, Shutaroh; Tsugita, Masanori; Iwai, Chizuo (Journal of Spine Research, 2020)
Vertebral osteomyelitis caused by non-tuberculous mycobacteria is uncommon, and there are only few reports in the literatures to date. It is characterized by progressive bony destruction and abscess formation. We report two patients who suffered from vertebral osteomyelitis caused by Mycobacterium Avium Complex (MAC). Those patients were successfully treated by two-staged posterior-anterior surgeries, i.e. posterior stabilization with spinal instrument followed by anterior debridement and autogenous strut bone grafting. After the surgery, infection was effectively controlled with apparent reduction of paravertebral abscess.